Investigating the Causality between Corruption and Economic Growth: A Systematic Review - Yusof, Muhammad Hafizuddin; Mohd Haniff, Muhammad Abu Hanifah; Kamaruddin, Zulaikha; Mohd Jaafar, Nurul Aifa; Saihani, Shamsul Baharin (Information Management and Business Review, 2023)
This study aims to establish a systematic examination of the existing literature pertaining to the causal relationship between corruption and its impact on a nation economic growth. In line with established methodological guidelines, particularly the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this research adopts a structured approach to comprehensively survey the relevant scholarly landscape. To construct a robust foundation for this investigation, a thorough search for scientific papers within the Scopus and Web of Science (WoS) databases, spanning the years from 2012 to 2022 was conducted. Our selection process ultimately led to the identification and analysis of seven publications that offer substantial empirical insights into the chosen domain of inquiry. Through a careful review of these research papers, a compelling pattern that corruption exerts a profound significant influence on various dimensions of economic growth within a nation emerged. Specifically, the synthesis of the extant literature suggests that corruption exhibits a discernible causative effect on critical economic parameters, notably including but not limited to purchasing power, country debt, political stability and foreign direct investment (FDI). In summary, the amalgamation of these scrutinized research findings underscores the substantial and multifaceted role of corruption as a causal factor in influencing economic growth dynamics. This investigation not only contributes to a deeper understanding of this critical relationship but also underscores the importance of anti-corruption measures in promoting sustained economic development and stability on a national scale.